Low Cost Airline Sales Promotion : in A Review - Ika Utami Yulihapsari (Indonesian Journal of Business Analytics, 2023)
In this scientific article want. provide a reinforcement of scientific articles with research results after that the researcher provides a perspective in this scientific article. this study's research methodology, which used variable-relevant journal mini-reviews of papers, was qualitative, metric table as below which will be displayed to display scientific articles to support literature study. concluded that it was proven true from the results of scientific articles found with sales promotion variables with the same research object, namely low cost carriers, where there were several scientific articles in their research results stating sales promotion significance with price and brand variables, as well as airline tickets, and the internet experience. Recommendations are in every finding of this scientific article. The point is that there are other variables in the field of marketing that can be used in future research.